Grappling with injustice: Corporate crime, multinational business and interrogation of law in context - Haines, Fiona (Theoretical criminology, 2021)
This article interrogates criminological ambivalence towards law as both essential in the control of corporate crime and as an enabler of corporate harm. It argues we can make sense of such tensions by seeing law—in its plurality of soft and hard forms—as constituent elements within multiple fields of struggle, in which laws operate as tools wielded to influence contested rules, and as rules governing regulatory struggles. This argument is developed by bringing criminological analyses of the law’s role in business facilitation and regulatory enforcement together with sociological analyses of ‘fields of struggle’. The value of this approach in illuminating law’s ambiguous role in relation to corporate harm is illustrated through two cases of multinational business activity in Indonesia.